2020
DOI: 10.15585/mmwr.rr6805a1
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Providing Quality Sexually Transmitted Diseases Clinical Services, 2020

Abstract: This report (hereafter referred to as STD QCS) provides CDC recommendations to U.S. health care providers regarding quality clinical services for sexually transmitted diseases (STDs) for primary care and STD specialty care settings. These recommendations complement CDC's Sexually Transmitted Diseases Treatment Guidelines, 2015 (hereafter referred to as the STD Guidelines), a comprehensive, evidence-based reference for prevention, diagnosis, and treatment of STDs. STD QCS differs from the STD Guidelines by spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 71 publications
4
99
0
2
Order By: Relevance
“…In low-resource settings, a visiting family and primary care physician or a trained doctor or nurse can provide these services while the appropriately trained teacher, school counsellor, or health worker provides promotive as well as some preventive and counselling services. [ 12 13 ] The school health service providers need to know the gender differences in the sexual behaviour and knowledge of prevention of STIs to provide adequate and effective sexual health services to students in schools. Research findings showed that knowledge about STI transmission might influence sexual behaviour and that knowledge is an important factor for the prevention of STIs.…”
Section: Introductionmentioning
confidence: 99%
“…In low-resource settings, a visiting family and primary care physician or a trained doctor or nurse can provide these services while the appropriately trained teacher, school counsellor, or health worker provides promotive as well as some preventive and counselling services. [ 12 13 ] The school health service providers need to know the gender differences in the sexual behaviour and knowledge of prevention of STIs to provide adequate and effective sexual health services to students in schools. Research findings showed that knowledge about STI transmission might influence sexual behaviour and that knowledge is an important factor for the prevention of STIs.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the number of sexual partners and choosing lower risk, safer sexual behaviors are also key opportunities for STI prevention. Additional STI prevention strategies are available to providers to help employ effective, quality clinical services 49,55 . Clinicians who cannot reliably deliver these services should refer patients to providers who provide comprehensive sexual and reproductive healthcare services.…”
Section: Personalized Sexual Health Discussionmentioning
confidence: 99%
“…Given concerns for AYA compliance or poor medication adherence, single‐dose regimens are preferred in this population 49 . Same‐day treatment can be easily dispensed, directly observed, and often completed while the patient is in the transplant clinic 55 . Patients diagnosed with an STI should be encouraged to abstain from further sexual encounters until both they and their partner(s) complete antimicrobial treatment.…”
Section: Strategies For Sti Preventionmentioning
confidence: 99%
“…The CDC recommends treatment not be delayed while waiting for diagnostic test results. Empiric, same day treatment may decrease complications (e.g., pelvic inflammatory disease) due to delayed care or loss to follow-up and reduce transmission ( 23 ).…”
Section: Post-analytical Challengesmentioning
confidence: 99%